From Murphy’s Christian Physicalism to Lowe’s Dualism - Jones, Mostyn; LaRock, Eric (TheoLogica: An International Journal for Philosophy of Religion and Philosophical Theology, 2021)
Nancey Murphy argues that God created us as physical beings without immortal souls. She supports this Christian physicalism by arguing that neuroscience can better explain minds in terms of physical information processing than dualists can in problematic nonphysical terms. We reply that Murphy overestimates neuroscience and underestimates dualism. She doesn’t show how neuroscience can explain the mind’s characteristic qualia, unity, privacy, or causality. We argue that Lowe’s dualism can better explain minds, often with experimental support and in testable ways. Murphy’s physicalism thus serves to highlight the value of Lowe’s dualism today.